Probing molecular forces in multi-component physiological membranes - Ray, Arjun; Gräter, Frauke; Thukral, Lipi (Physical chemistry, chemical physics, 2018)
Biological membranes are remarkably heterogeneous, composed of diverse lipid mixtures with distinct chemical structure and composition. By combining molecular dynamics simulations and the newly developed Lipid-Force Distribution Analysis (L-FDA), we explore force transmission in complex multi-component membrane models mimicking eukaryotic organelles. We found that the chemical-moiety based segmentation at membrane interfaces revealed a distinctive distribution of bonded and non-bonded forces in diverse membrane environment. Our molecular stress analysis could have far-reaching implications in describing the relationship between membrane mechanical properties and functional states of chemically distinct lipids.
First published on 27 Nov 2017
Gesehen am 29.05.2019